IMPLEMENTASI KEBIJAKAN MAGANG DAN KONSELING WARGA BERKEBUTUHAN KHUSUS DI SURABAYA - Ghulam, Zainil (Institut Agama Islam Syarifuddin Lumajang, 2020)
This article discusses counseling and internship programs for people with special needs that are run by the Surabaya City Government. As mandated by the 1945 Constitution, it is the state's obligation to protect the rights of persons with special needs. Including, their rights in the scope of employment. The Surabaya City Government prepared an apprenticeship program for them. Before that, there was a counseling process for each person with special needs. In the implementation of national development aimed at realizing a just and prosperous society based on Pancasila and the 1945 Constitution, people with special needs are part of Indonesian society who also have the same position, rights, obligations and roles. In many cases, apprentices are then recruited by the company. This program is carried out in collaboration with a number of institutions or companies in Surabaya. The theory used in this article is counseling and public policy. While the method used is qualitative, with a literature review approach. As a result, what the Surabaya City Government is doing reinforces the psychological aspects of school graduates with special needs. During the internship, they gained valuable experience and boosted the confidence of each participant. Even if they are not immediately recruited to work at the place, the post-apprenticeship certificate they have, can be their reinforcement when they want to apply to other companies. So, the benefits of this program are in the aspect of training for them, and promotion of the performance of those who are not less than those who do not have some special needs.